2020
DOI: 10.1002/cam4.3253
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dutch version of the Edmonton Symptom Assessment System

Abstract: Background The Utrecht Symptom Diary (USD) is a Dutch and adapted version of the Edmonton Symptom Assessment System, a patient‐reported outcome measurement (PROM) tool to asses and monitor symptoms in cancer patients. This study analyses the validity and responsiveness of the USD and the cutoff points to determine the clinical significance of a symptom score. Methods Observational longitudinal cohort study including adult in‐ and outpatients treated in an academic hospital in the Netherlands who completed at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…[5][6][7]33,[56][57][58][59] Additionally, we calculated the mean values of the ESAS-TOT scores, and ESAS-PHY and ESAS-PSY symptom distress sub-scores. Furthermore, we used the concept of the scoring stratification of 0 (no symptom), 1-3 (mild), 4-6 (moderate) and 7-10 (severe) 5,18,21,22,32,34,51,53,[55][56][57][58]60 , to stratify the calculated ESAS-TOT symptom scores into TOT-low (0-8), TOT-mild , TOT-moderate and TOT-severe (63-90); ESAS-PHY sub-scores into PHY-low (0-5), PHY-mild (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), PHYmoderate (24)(25)(26)(27)(28)(29)(30)(31)(32)…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[5][6][7]33,[56][57][58][59] Additionally, we calculated the mean values of the ESAS-TOT scores, and ESAS-PHY and ESAS-PSY symptom distress sub-scores. Furthermore, we used the concept of the scoring stratification of 0 (no symptom), 1-3 (mild), 4-6 (moderate) and 7-10 (severe) 5,18,21,22,32,34,51,53,[55][56][57][58]60 , to stratify the calculated ESAS-TOT symptom scores into TOT-low (0-8), TOT-mild , TOT-moderate and TOT-severe (63-90); ESAS-PHY sub-scores into PHY-low (0-5), PHY-mild (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), PHYmoderate (24)(25)(26)(27)(28)(29)(30)(31)(32)…”
Section: Discussionmentioning
confidence: 99%
“…These side effects can burden patients' physical and psychological wellbeing to the extent that in some cases treatment may be postponed or discontinued. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Therefore, it is essential for patients to be able to effectively communicate any adverse effects they are experiencing to their healthcare providers. Several studies [4][5][6]8,10,12,[18][19][20][21][22][23][24][25][26][27][28][29][30] have reported that systematic self-reporting of patients' symptoms during their cancer journey has facilitated appropriate intervention, allowed patients to communicate their most relevant physical symptoms and psychosocial concerns to their healthcare providers and revealed the impact of cancer and treatment from patients' perspective.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations